Influence of career decision-making self-efficacy, career maturity, parenting style, and parental perfectionism on career decision among undergraduate students - Khasmohammadi, Mahdi (2018)
Career decision is one of the most investigated constructs in career development. Numerous studies assume that career decision is associated with various personal or external factors. Given that one of the primary goals of career counseling is to assist with the career decision-making process, research in this area is crucial. Therefore, the primary rationale for this study was to be the first known investigation into the relationship between parental perfectionism, parenting style, career decision self-efficacy, career maturity, and career indecision. This research was an initial attempt to integrate and extend existing research in the areas of parenting and career development using the less studied construct of parental perfectionism and to investigate whether gender plays a moderating effect on the relationships between exogenous variables and career indecision among undergraduate students. The multi-stage cluster random sampling method was employed to recruit a total of 543 undergraduate students aged 18 to 24 years from public universities in the Selangor state. Descriptive and correlational research design was employed. The respondents completed Career Decision Scale (CDS; Osipow, 1987), Career Decision Self-Efficacy Scale – Short Form (CDSE-SF, Betz et al., 1996), Career Maturity Inventory-Revised (CMI-R; Crites and Savickas, 1996), Parental Authority Questionnaire-Revised (PAQ-R; Reitman et al., 2002), and Family Almost Perfect Scale (FAPS; Wang et al., 2010). Structural Equation Modeling (SEM) indicated that undergraduate students with low career maturity and low career decision making self-efficacy were more likely to report high career indecision. Moreover, this study supported the moderating role of gender between career decision making self-efficacy with career indecision. Furthermore, parental perfectionism was the strongest predictor of career indecision among undergraduate students. The findings of this study also proposed that career maturity, career decision making self-efficacy, parenting style and parental perfectionism were valuable predictors of career indecision among undergraduate students. Overall, studied variables were explained 64% of the variance in career indecision. The current study advances understanding on the importance of career maturity and career decision making self-efficacy as influencing individual factors against career indecision. The findings of the study also provided evidence to increase understanding on the importance of parenting styles and parental perfectionism as external factors on career indecision among undergraduate students. The findings of the current study can be useful for counselors, therapists, educators, parents, and policy makers for prevention and intervention of career indecision among undergraduate students. However, more studies are needed to investigate the role and impact of parental perfectionism in career indecision.